Programming for Preventive Disease and Improved Production in Sheep - Boundy, T. (1981)
Sheep losses each year are high in all types of rearing systems throughout the United Kingdom. Losses could well be reduced by a closer relationship between the sheep owner and the veterinarian. A closer relationship should involve the development of a simple disease preventive programme requiring a number of regular farm visits each year. Any such programme could attempt to control disease mainly by preventive methods, establish a complete parasite control programme and incorporate a high degree of instruction. There is probably a need for many veterinarians to attend specialist sheep courses, and suggestions are offered whereby the situation could be improved.